Potensi Desa Wisata Rende - Handrianus V.M Wula (Program Studi Imu Pemerintahan, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Timor, 2019)
Tourism villages were formed as one of the manifestations of the Indonesian government in empowering rural communities through the development of the tourism sector. Rende Village is one of the two tourism villages in East Sumba. The aim of the research is to describe the potency of Rende tourism village as a traditional village at East Sumba. The author uses descriptive research with qualitative approach. This village has cultural properties such as traditional villages, tombs megalithic and traditional ikat crafts. The cultural wealth can be enjoyed in the Praiyawang traditional village. The government and local villagers need to work together in optimizing community empowerment through a village tourism program.